[Afisz. Incipit:] Krakowski kwartet smyczkowy. (Gdańsk : [wydawca nieznany], 1954)
Afisz informujący o koncercie w Grand Hotel 23.02.1954 r.
Keywords: Grand Hotel (Sopot); 1901-2000; 1945-1989; Sopot (woj. pomorskie); Druki ulotne